Factors Affecting Low Buffalo Ownership in Sumbang Village, Curio Sub District, Enrekang District - Kartika Kartika; S. N. Sirajuddin; I. Rasyid (Jurnal Ilmu dan Teknologi Peternakan, 2016)
This research aimed to study factors affecting low number of buffaloes ownership in Sumbang village, Curio Sub district, Enrekang District. This is an explorative research aiming to collect more information related to the problems and social phenomena that happened in the community. Descriptive analysis used was explorative analysis which was based on the factors contributed to lower number of buffaloes ownership in Sumbang village, Curio Sub district, Enrekang District using Delphi method. Data collection process was conducted three times using questionnaire that has been prepared beforehand. The result of study indicated that there were five factors that contributed to the lower number of buffaloes ownership in the area, namely limited feeding with 87 score asthe first rank, limited capital scoring 93 as the second rank, no or limited labor as the third rank with 136 score, less bull as the fourth rank scoring 166, and low calving scoring 176 as the fifth rank.